Assessment of standalone streetlighting energy storage systems based on hydrogen of hybrid PV/electrolyzer/fuel cell/ desalination and PV/batteries. (July 2023) - Nasser, Mohamed; Hassan, Hamdy
Abstract: Expanding the scope of renewable energy consumption is essential to achieve the aim of a sustainable and carbon neutrality society. Hydrogen could be considered the future form of the leading energy system for multipurpose applications. In the current study, the performance of a standalone streetlighting photovoltaic hydrogen storage system (PV/H2 ) via hybrid polymer electrolyte membrane/fuel cell/single effect desalination system (PV/PEM/FC/SED) is investigated and compared with the traditional (PV/Battery) system. A complete mathematical model of the two systems is constructed. A MATLAB/Simulink code is developed to simulate both systems under the actual climatic conditions of New Borg El-Arab City, Egypt. The results indicate that the yearly load is 19, 745 kWh, which can be fulfilled with 160 m 2 of PV panels in the case of PV/H2 and 40 m 2 for the PV/Battery system. In addition, the overall system efficiency is 8.5 % and 17.8 % for the hydrogen and battery system, respectively. Although the battery system is more efficient than the hydrogen system, the latter is more economical. The Levelized cost of electricity for the PV/H2 is 1.06 $/kWh with a payback period of 6.44 years compared with 2.8 $/kWh and 11.7 years for PV/Battery systems. Therefore, the hydrogen system is recommended for supplying electricity demand. The system reduces CO2 emissions by up to 25.6 Tons per year with up to 1024$ annual gain. Highlights: Standalone storage PV/hydrogen and PV/battery systems for streetlighting are studied. Overall system efficiency is 8.5 % and 17.8 % for hydrogen and battery system, respectively. LCE is about 1.06 $/kWh and 2.8 $/kWh for PV/H2 and PV/Battery systems, respectively. PV/H2 system has a 6.44-year PBP, while PV/Battery has 11.7 years.